Vídeos no ensino e aprendizado de vocabulário em língua inglesa : uma abordagem léxico-visual - Monteiro, Leila Maria Taveira (2010)
The aim of this study is to contribute to the discussion on vocabulary teaching and learning in the classroom of English as a foreign language, with an emphasis on the need for meaning construction to be perceived and realized in chunks of language, rather than in isolated words. The theoretical background of the research is based on studies which focus on lexical acquisition as a crucial aspect in the process of foreign language acquisition. The approach of the study combines the lexical dimension and the multimodal perspective. The latter points to the growing importance of multimedia learning, in a society in which images are more and more predominant. Regarding the objective of the study, we use concepts from the model of Kress and Van Leeuwen, as well as the work of Mayer for theoretical support. Kress and Van Leeuwen call for a new concept of literacy which includes the visual modalities, while Mayer argues that there is an urgent need for the appropriate use of multimediatic resources in the classroom environment. The results produced/yielded by the research intervention suggest that the use of multimedia instruments may contribute to the process of vocabulary acquisition in the foreign language classroom and open space for further studies in the area.